Super-optimizing analysis and Philippine policy problems - Nagel, Stuart S. (1991)
Super-optimum solutions to public policy problems involve finding alternatives that enable conservatives, liberals, and other major viewpoints to all come out ahead of their best initial expectations simultaneously. This mode of analysis can be applied to any public policy problem, including such Philippine problems as deciding on a minimum wage, trying to commute to and from Manila, reforming land ownership, dealing with multiple languages in Philippine education, and handling the American military bases. Such solutions are facilitated by well-placed subsidies and tax breaks, systematic policy analysis, decision-aiding software, democratic institutions, and positive creative thinking.
Keywords: Policymaking; Super-Optimum Solutions (SOS)